Health-related quality of life and its associated factors: results of a multi-center cross-sectional study among university students. (26th February 2019) - Backhaus, Insa; D'Egidio, Valeria; Saulle, Rosella; Masala, Daniele; Firenze, Alberto; De Vito, Elisabetta; Mannocci, Alice; La Torre, Giuseppe
Abstract: Background: The decline of health among university students represents an important and growing public health concern. Health problems and unhealthy lifestyle habits are common among many students, but factors influencing students' health are not fully understood. Methods: Italian university students from different study programs and curriculum years were asked to fill out a self-administered questionnaire, collecting data about age, gender, curriculum year, study program and health-related quality of life (QOL). Two latent factors were extracted: physical component summary score and mental component summary score. T -test, one-way ANOVA, multivariate and age and sex-stratified analyses were performed. Results: Students scored relatively poor on health-related QOL, with an overall mental component summary score of 41, 3% (± 10, 0) and physical component summary score of 52, 9% (±6, 0), with significantly higher mental component summary score for male students ( P = < 0, 005). Studying economics, law ( b = −2, 513, P = 0, 007) or engineering ( b = −2, 762; P = 0, 001) was associated to negatively influence students' health. Conclusions: Factors such as study program are associated with health-related QOL. Further longitudinal studies assessing additional socio-demographic factors are needed to fully assess what influences students' health. Students' health should be at the top of the agenda of public health researchers, academic supervisors and policy-makers.